2012
DOI: 10.1002/jmv.23342
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and epidemiological features of gastroenteritis outbreaks involving genogroup I norovirus in Victoria, Australia, 2002–2010

Abstract: GI noroviruses are relatively rare and systematic studies of the molecular epidemiology of GI norovirus outbreaks are lacking. The current study examined the molecular virology of GI norovirus outbreaks in Victoria, Australia (2002-2010). Of 1,617 norovirus outbreaks identified, 69 (4.3%) were associated with GI norovirus alone, 1,540 (95.2%) with GII norovirus alone and 8 (0.5%) with GI + GII. Some differences between GI and GII outbreak epidemiology were found. GI outbreaks peaked in the 2-month period Novem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
25
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 21 publications
0
25
0
Order By: Relevance
“…GII noroviruses, especially the GII.4 strains, are the predominant cause of gastroenteritis, both in outbreaks and in sporadic cases worldwide (30). The prevalence and outbreak activity of the GI genogroup, which is the second most predominant genogroup, are limited (33), and reports of GIV around the world are also rare (34).…”
Section: Discussionmentioning
confidence: 99%
“…GII noroviruses, especially the GII.4 strains, are the predominant cause of gastroenteritis, both in outbreaks and in sporadic cases worldwide (30). The prevalence and outbreak activity of the GI genogroup, which is the second most predominant genogroup, are limited (33), and reports of GIV around the world are also rare (34).…”
Section: Discussionmentioning
confidence: 99%
“…GI NoVs, apart from NV, are not as well studied and understood as their GII counterparts due to their lower prevalence. Recent epidemiological studies, however, show an increase in the prevalence of GI outbreaks worldwide, with different genotypes such as GI.4, GI.6, GI.3, and GI.7 predominating in different geographical regions (9)(10)(11)(12)(13). A study from Alberta, Canada, showed that GI NoVs were responsible for ϳ37% of all NoV infections from late 2012 to early 2013, with the majority being caused by GI.6 and GI.…”
mentioning
confidence: 99%
“…Based on sequence variations in ORF2, 8 GI genotypes and at least 21 GII genotypes have been described using the numeric designation for the various strains (3,4,5). Another 14 GI genotypes and at least 29 GII genotypes have been described using numeric or alphabetic designations based on variations in ORF1.…”
mentioning
confidence: 99%
“…Our understanding of NoV GI genetic evolution and outbreak activity are limited due to the overall low prevalence of GI outbreaks (4). GI strains appear to be more common in outbreak settings other than health care facilities, and different GI genotypes predominate over time (4,10).…”
mentioning
confidence: 99%
See 1 more Smart Citation